Hubungan Antara Motivasi Siswa Dan Efektivitas Proses Pembelajaran Pada Mata Pelajaran IPS Kelas IX Di SMP Katolik St. Theresia Kupang - Siprianus See (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
The purpose of this observation is to determine correlation between student motivation and the effectivness of theaching and learning process in social subject to the ninth year class of SMP Katolik St.Theresia Kupang. This is quantitative research. The subject of the research is 93 ninth year class of SMP Katolik Theresia Kupang. The Data was analized by using product moment correlation and followed by regression. The result of product moment correlation and regression, There is possitive correlation and significant between student motivation with the effectivness of teaching and learning process in social subject to the ninth year class of SMPK St.Theresia Kupang, with correlation coefficient score = 0,633 and probability sig = 0,000 > 0,05 or t score = 7,790 > t table = 1,671. Meanwhile determination coefficient or effective support variable student motivation to the effectivness of teaching and learning process in social subject to the ninth year class of SMPK St.Theresia Kupang is R Square = 0,400 x 100% = 40%.